Study the outpatients' prescription pattern of antibiotics in paediatric populations of two hospitals - Katta Venkatesh Ramanath; B. V. B. Balaji (Archives of Global Professionals, 2013)
Objective: To assess the outpatients prescription pattern of antibiotics in paediatric population of a rural and an urban hospital. Materials and Methods: A prospective, cross-sectional and interventional study was carried out in the paediatric departments of Adichunchanagiri Hospital and Research Centre and Jabilli Children HospitalRajahmundry for a period of 7 months, after taking permission from the ethics committee. The consent/assent of the patients was taken, and their data and prescription information was collected by using a patient data collection form This was done for a period of 3 months in each hospital. The collected information was subjected for suitable statistical analysis. Results: A total of 1170, hospital 1: 915/218 and hospital 2: 255/175, prescriptions were screened. Out of which 218 and 175 were contained antibiotics, and the average number of drugs was (2.84 ± 0.11) and (3.61 ± 0.15) for hospital 1 and 2, respectively. The prescriptions contained only one antibiotic. No drug interaction (DI) and adverse drug reactions (ADRs) were found. Most common diseases found were lower respiratory tract infections (LRTI) and upper respiratory tract infections (URTI) (hospital 1), and fever and LRTI (hospital 2). Commonly prescribed antibiotic class and drugs was penicillin-amoxicillin (hospital 1), cephalosporins-cefixime, cefuroxime, and cefalexin (hospital 2). The antibiotic combination used was amoxicillin + clavulanic acid. The average total prescription cost and antibiotic cost was Rs. 106.66 and Rs. 70.32 (hospital 1), and Rs. 245.41and Rs. 113.32 (hospital 2), respectively. Conclusion : The prescribing pattern of antibiotics was rational in both the hospitals.